Optogenetic Manipulation of Postsynaptic cAMP Using a Novel Transgenic Mouse Line Enables Synaptic Plasticity and Enhances Depolarization Following Tetanic Stimulation in the Hippocampal Dentate Gyrus - Luyben, Thomas T.; Rai, Jayant; Li, Hang; Georgiou, John; Avila, Ariel; Zhen, Mei; Collingridge, Graham L.; Tominaga, Takashi; Okamoto, Kenichi (Frontiers in Neural Circuits, 2020)
cAMP is a positive regulator tightly involved in certain types of synaptic plasticity and related memory functions. However, its spatiotemporal roles at the synaptic and neural circuit levels remain elusive. Using a combination of a cAMP optogenetics approach and voltage-sensitive dye (VSD) imaging with electrophysiological recording, we define a novel capacity of postsynaptic cAMP in enabling dentate gyrus long-term potentiation (LTP) and depolarization in acutely prepared murine hippocampal slices. To manipulate cAMP levels at medial perforant path to granule neuron (MPP-DG) synapses by light, we generated transgenic (Tg) mice expressing PAC (photoactivatable adenylyl cyclase) in DG granule neurons. Using these Tg(CMV-Camk2a-RFP/bPAC)3Koka mice, we recorded field excitatory postsynaptic potentials (fEPSPs) from MPP-DG synapses and found that photoactivation of PAC during tetanic stimulation enabled synaptic potentiation that persisted for at least 30 min. This form of LTP was induced without the need for GABA receptor blockade that is typically required for inducing DG plasticity. The paired-pulse ratio (PPR) remained unchanged, indicating the cAMP-dependent LTP was likely postsynaptic in nature. By employing fast voltage-sensitive dye (VSD: di-4-ANEPPS) and fluorescence imaging, we found that photoactivation of the PAC actuator enhanced the intensity and extent of dentate gyrus depolarization triggered following tetanic stimulation. These results demonstrate that the elevation of cAMP in granule neurons is capable of rapidly enhancing synaptic strength and neuronal depolarization. The powerful actions of cAMP are consistent with this second messenger having a critical role in the regulation of synaptic function.